Hippoterapia u pediatrických pacientov = Hippotherapy in paediatric patients - Shtin Baňárová, Patricia; Malay, Miroslav; Černický, Miroslav; Kováčová, Katarina; Zverbíková, Jana; Petríková Rosinová, Iveta; Grabczak, Pavel (Vilnius: Mykolas Romeris Universitetas)
The horse has been accompanying humans since ancient times, and has been used in transport, agriculture and horses find their effective use in sport as well. Nowadays, horses are also used globally in the rehabilitation process. Hippotherapy can influence the entire personality of the child, not only on the physical (motor) side, but also in the degradation of pathological movement stereotypes, relaxation of increased muscular tension, equilibrium training, but also psychologically through the removal of distrust, feeling of fear, increasing self-confidence or feeling of responsibility. Last but not least, thanks to hippotherapy, the child's cognitive functions such as perception, thinking, learning or attention are also improved.
Keywords: hipoterapia; dziecko; hippotherapy; child